1994
DOI: 10.1159/000244102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mode of Delivery, Parity and Umbilical Blood Gas on First Meconium Passage in Full-Term Healthy Neonates

Abstract: The various physiologic factors which might influence the time of first meconium passage were studied in 62 healthy full-term newborn infants. Thirty-two babies were born vaginally and 30 by elective cesarean section. Infants born vaginally were more acidotic and passed first stool earlier compared to those born by cesarean section. The same applies to vaginally delivered babies when comparing babies born to primipara and others. Acidosis is a presumed mechanism, and a role of gastrointestinal hormones is sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
2
8
1
3
Order By: Relevance
“…Our study did not support this relationship. Tateishi et al reported that vaginally born infants pass their meconium earlier than cesarean section born infants [18]. In our study, there was no relationship between the method of birth and the timing of stool, as reported previously [13].…”
Section: Timing Of the First Meconium Stoolsupporting
confidence: 78%
“…Our study did not support this relationship. Tateishi et al reported that vaginally born infants pass their meconium earlier than cesarean section born infants [18]. In our study, there was no relationship between the method of birth and the timing of stool, as reported previously [13].…”
Section: Timing Of the First Meconium Stoolsupporting
confidence: 78%
“…Evaluating 32 infants born vaginally and 30 infants born after elective c/s, vaginally born infants were more acidotic and passed their first stools earlier. Acidosis is another presumed mechanism, and a role for gastrointestinal hormones is suggested to be the possible mediator of increased gastrointestinal motility in these infants [26]. However, mean meconium passage time was similar in infants born vaginally or with c/s in our study.…”
Section: Discussioncontrasting
confidence: 59%
“…Passage of an infant's first meconium stool is often used as a screen for a normal GI tract. [1][2][3][4] Two studies in the American population state that 94% 5 and 98.5% 6 of term infants had their first meconium stool by 24 hours. These studies were performed some time ago when practices in the normal newborn nursery were likely quite different from current practices.…”
Section: Introductionmentioning
confidence: 99%
“…These studies did not examine the type and schedule of feedings. In recent studies in Asia, [2][3][4] the contribution of different physiologic factors (sex, gestational age, birth weight, type of delivery, Apgar scores) to time to first meconium stool was evaluated. There have been no studies that have evaluated the contribution of first 24 hours' feeding type to time to first meconium stool, directly comparing breastfeeding vs formula feeding.…”
Section: Introductionmentioning
confidence: 99%